Review of life cycle assessment of nanomaterials in photovoltaics. (August 2016) - Kim, Junbeum; Rivera, Julio L.; Meng, Toon Yong; Laratte, Bertrand; Chen, Sha
Highlights: A critical review on applied life cycle assessment (LCA) and nanomaterials in PVs. Identified and discussed on research gaps and opportunities in LCA and nanomaterials in PVs. Intensive researches on the end-of-life stage of the PVs are required. Abstract: Photovoltaic (PV) technologies are gaining a share in the renewable energy production market. Recently nanomaterials have been used by researchers to improve the performance and efficiency of PVs. Consideration to the environmental aspects of nanomaterials infused PVs is a growing area of interest. Therefore, the objective of this paper is to investigate the application of LCA to PV technology. Particularly, the authors are interested in scrutinizing the application of LCA to PV systems infused with nanomaterials. In this paper, a literature review was performed to describe and assess the limitations of current research on the usage of life cycle assessment (LCA) methodologies to predict the environmental impact of nanomaterials usage on PVs. The approach to this review focuses on two sub-categories: production and/or use of PVs, and end-of-life of PVs. Following this approach the context and progress of LCA is described. Research gaps and opportunities for improved environmental performance throughout the life cycle of nano-infused PVs are identified and discussed. This work provides a basis for the continue analysis of emerging nanomaterials and PV technologies.